STRATEGI GURU DALAM MENGATASI ANAK SLOW LEARNER DALAM PEMBELAJARAN MATEMATIKA KELAS VI MADRASAH IBTIDAIYAH SWASTA TARBIYAH TEBAS TAHUN 2024-2025 - Ririn Padilah; Suhari; Hadisa Putri (CV. ADIBA AISHA AMIRA, 2026)
The purpose of this study is to analyze: (1) teachers' strategies in mathematics learning in Grade VI at Tarbiyah Tebas Private Madrasah Ibtidaiyah, (2) the characteristics of slow learner students in mathematics learning in Grade VI at Tarbiyah Tebas Private Madrasah Ibtidaiyah, and (3) teachers' strategies to address slow learner students in mathematics learning in Grade VI at Tarbiyah Tebas Private Madrasah Ibtidaiyah. This study employs a qualitative approach with a case study research design. Data collection techniques include interviews and observations. The data analysis techniques used are data reduction, data display, and conclusion drawing. The techniques for checking the validity of the data are triangulation and member checking. The results of this study indicate that: (1) the learning strategies implemented by teachers are oriented toward a student-centered approach, with the teacher acting as a facilitator. Various learning models are applied, including cooperative learning, contextual learning, problem-solving, and discovery learning, supported by the use of diverse methods and media such as teaching aids, educational games, and interactive videos. These strategies are able to increase student participation, collaboration, and facilitate the understanding of slow learner students. (2) the characteristics of slow learner students in mathematics learning are marked by difficulties in understanding abstract concepts, slower problem-solving abilities, a tendency to lose concentration easily, a need for more time, and weak memory. These conditions impact their low interest in participating in mathematics learning. (3) teachers implement strategies through curriculum modification, simplification of materials, individual guidance, remedial teaching, the use of engaging media, and the application of cooperative learning through peer tutoring and group discussions. Teachers also use simple language, provide repetition of material, and give exercises gradually and repeatedly. With these strategies, slow learner students are better supported in understanding the material and participating more effectively in the learning process.